Coaxially Bioprinted Cell-Laden Tubular-Like Structure for Studying Glioma Angiogenesis - Wang, Xuanzhi; Li, Xinda; Zhang, Yi; Long, Xiaoyan; Zhang, Haitao; Xu, Tao; Niu, Chaoshi (Frontiers in Bioengineering and Biotechnology, 2021)
Glioblastomas are the most frequently diagnosed and one of the most lethal primary brain tumors, and one of their key features is a dysplastic vascular network. However, because the origin of the tumor blood vessels remains controversial, an optimal preclinical tumor model must be established to elucidate the tumor angiogenesis mechanism, especially the role of tumor cells themselves in angiogenesis. Therefore, shell-glioma cell (U118)-red fluorescent protein (RFP)/core-human umbilical vein endothelial cell (HUVEC)-green fluorescent protein (GFP) hydrogel microfibers were coaxially bioprinted. U118–RFP and HUVEC–GFP cells both exhibited good proliferation in a three-dimensional (3D) microenvironment. The secretability of both vascular endothelial growth factor A and basic fibroblast growth factor was remarkably enhanced when both types of cells were cocultured in 3D models. Moreover, U118 cells promoted the vascularization of the surrounding HUVECs by secreting vascular growth factors. More importantly, U118–HUVEC-fused cells were found in U118–RFP/HUVEC–GFP hydrogel microfibers. Most importantly, our results indicated that U118 cells can not only recruit the blood vessels of the surrounding host but also directly transdifferentiate into or fuse with endothelial cells to participate in tumor angiogenesis in vivo. The coaxially bioprinted U118–RFP/HUVEC–GFP hydrogel microfiber is a model suitable for mimicking the glioma microenvironment and for investigating tumor angiogenesis.